Editorial Foreword - Anthony Reid (Center for Southeast Asian Social Studies (CESASS), 2018)
It is a pleasure to introduce this second issue of the enterprising new journal, IKAT: The Indonesian Journal of Southeast Asian Studies. It is breaking new ground in opening Indonesia to its region, and establishing a high standard of scholarly publication in English. It is good to see Southeast Asians taking up the challenge of understanding their own region. As the Orientalist tradition of Europe weakens, institutions and individuals in the region must take up the challenge of understanding, preserving and analyzing Southeast Asian cultures, many of them endangered. Southeast Asian Studies must return to Southeast Asia, and IKAT is certainly helping this process.